2014
DOI: 10.1038/leu.2014.275
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20 therapy induces a memory Th1 response through the IFN-γ/IL-12 axis and prevents protumor regulatory T-cell expansion in mice

Abstract: The long-lasting clinical response by lymphoma patients to anti-CD20 therapy has been attributed to the induction of an anti-tumor adaptive immunity. We previously demonstrated that a CD4-dependent mechanism is responsible for the long-term protection of CD20(+) tumor-bearing mice by anti-CD20 treatment. Here, we compare tumor immunity in tumor-bearing animals that did or did not receive anti-CD20 treatment. Splenic CD4(+)FoxP3(+) regulatory T cells (Tregs) expanded substantially in untreated mice that exhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
53
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 37 publications
1
53
0
1
Order By: Relevance
“…30 In murine models some studies report a primary role for phagocytic mechanisms. 26, 31, 32, 33 However, others have demonstrated the importance of ADCC by NK cells and these studies used a similar EL4hCD20 model to ours, 19, 20 suggesting that the mechanism of action may vary depending on the tumor model, location and antibody isotype. Here we have demonstrated that for obinutuzumab, when given in combination with a systemic TLR7 agonist, long-term tumor-free survival appears to be dependent on NK cells and CD4 + T cells with macrophages and monocytes only able to mediate short-term increases in survival.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…30 In murine models some studies report a primary role for phagocytic mechanisms. 26, 31, 32, 33 However, others have demonstrated the importance of ADCC by NK cells and these studies used a similar EL4hCD20 model to ours, 19, 20 suggesting that the mechanism of action may vary depending on the tumor model, location and antibody isotype. Here we have demonstrated that for obinutuzumab, when given in combination with a systemic TLR7 agonist, long-term tumor-free survival appears to be dependent on NK cells and CD4 + T cells with macrophages and monocytes only able to mediate short-term increases in survival.…”
Section: Discussionmentioning
confidence: 65%
“…A type I anti-CD20 mAb was previously shown to eradicate EL4hCD20 cells in C57Bl/6 mice by the same mechanism. 19, 20 Taken together with data that R848 and other TLR agonists can increase levels of activating FcγR but decrease levels of the inhibitory FcγRIIb, 21, 22 this suggests that R848 is potentiating obinutuzumab effector mechanisms, in particular ADCC by NK cells, rather than priming other immunological pathways. Indeed, in vivo priming of NK cells with R848 was necessary for enhanced IFNγ production by NK cells upon engagement of Fc receptors by obinutuzumab.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…This was a direct effect of IFNγ or Nrp1 −/− T reg -derived IFNγ as no other cells types were included in the in vitro experiments. Previous studies have suggested that IL12 can impact T reg suppression and induce IFNγ expression (Dominguez-Villar et al, 2011; Koch et al, 2012; Zhao et al, 2012), while others show that IFNγ can limit T reg expansion (Deligne et al, 2015; Olalekan et al, 2015; St Rose et al, 2013; Visperas et al, 2014). However, the direct effect of IFNγ on T reg function in vivo had surprisingly not been appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…In the late stage of the treatment, CD4 + T cells in the treated mice were differentiated into predominant Th1, CD4 + CTL and Tfh subsets, which could maintain long-term antitumor immunity. By far, hyperthermia, therapeutic vaccines (dendritic cell vaccine) and antitumor mAb treatment are shown to mainly drive differentiation of CD4 + T cells into Th1 cells, 39, 40, 41, 42 whereas multiple CD4 + T-cell lineages induced by the therapeutic strategies participated in antitumor immunity has not been reported. This study revealed that multiple CD4 + T-cell lineages differentiation was significantly dominated at the different stage after the treatment, which would be a characteristic hallmark of long-term CD4 + T-cell immunity triggered by the treatment.…”
Section: Discussionmentioning
confidence: 99%